subtract the sum of 3x²+2xy-2y² and 5y²-7xy from 5x² from 5x²-2y²-3xy
Attachments:
![](https://hi-static.z-dn.net/files/d4a/f644c5a1140feab314ecf5107468a7be.jpg)
Answers
Answered by
4
Your answer is in the attachment.
hope it will help you.
please mark it as brainliest.
Attachments:
![](https://hi-static.z-dn.net/files/d90/bb4906e5995220e583117955d82862ec.jpg)
Answered by
4
Answer:
First,
(3x²+2xy-2y²) + (5y²-7xy)
= 3x²+2xy-2y²+5y²-7xy
= 3x²+2xy-7xy+5y²-2y²
= 3x²-5xy+3y²
Now,
(3x²-5xy+3y²) - (5x²-2y²-3xy)
= 3x²-5xy+3y²-5x²+2y²+3xy
= 3x²-5x²-5xy+3xy+3y²+2y²
= -2x²-2xy+5y²
Similar questions